COST UTILITY ANALYSIS PENGOBATAN HEMODIALISIS PASIEN GAGAL GINJAL KRONIK DI RUMAH SAKIT PEMERINTAH DAN SWASTA DI KALIMANTAN SELATAN - Maulidie Alfiannor Saputera, Mochammad; Ismail, Hasan; Rio Pambudi, Didik; Rahmadina, Aprillia; Muslim, Muhamad (Universitas Borneo Lestari, 2025)
Health care costs have continued to increase over time in patient treatment. Cost-utility analysis, a branch of pharmacoeconomic evaluation, assesses patient utility in relation to incurred costs. Chronic kidney disease (CKD) is among the most prevalent diseases in South Kalimantan; therefore, this study aimed to analyze the cost-utility of CKD patients undergoing hemodialysis. This research employed a cross-sectional design conducted in two hospitals as comparison sites, with a total of 43 participants (16 from a private hospital and 27 from a public hospital). Data were collected prospectively using the validated and reliable EQ-5D-5L questionnaire and Visual Analog Scale (VAS) to assess patient health status, along with observation sheets for cost data. The results showed that the Cost Utility Ratio (CUR) in the private hospital was Rp 78,928.88, while in the public hospital it was Rp 159,868.76, yielding an Incremental Cost Utility Ratio (ICUR) of Rp 8,626.80 per QALY. In conclusion, the private hospital demonstrated better cost-utility compared to the public hospital in providing hemodialysis treatment for CKD patients, as indicated by the ICUR value.